2014
DOI: 10.1007/s10584-014-1171-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards fair local outcomes in adaptation to sea-level rise

Abstract: Arguments that fairness should be a guiding principle of climate change adaptation have been primarily concerned with distributive and procedural aspects of fairness, with far less attention paid to the temporal, spatial and interactional dimensions of fairness. This paper presents the results of a study that sought to understand the multiple dimensions of fairness of adaptation strategies that exist or can be developed to deal with sea-level rise. The study focused on five small communities along the south-ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 26 publications
0
39
0
1
Order By: Relevance
“…If, like Graham et al (2015), we consider distributive and procedural justice to be intertwined, it is important to consider the ways in which these effects (on individuals and communities) might be shaped by the process of decision-making. to (re)produce this inequality at multiple scales, in sometimes unexpected ways.…”
Section: Discussionmentioning
confidence: 99%
“…If, like Graham et al (2015), we consider distributive and procedural justice to be intertwined, it is important to consider the ways in which these effects (on individuals and communities) might be shaped by the process of decision-making. to (re)produce this inequality at multiple scales, in sometimes unexpected ways.…”
Section: Discussionmentioning
confidence: 99%
“…Here we advance a typology of moral intuitions related to climate adaptation (Table 1). It is based on prior descriptions of moral foundations, and builds on significant theory and evidence of the ethics and social challenges of adaptation and social differentiation in vulnerability to the impacts of climate change (Adger et al, 2009, Thomas and Twyman 2005, Dow et al 2006, Paavola and Adger 2006, Graham et al 2015.…”
Section: Moral Reasoning For Adaptation Dilemmas: a Conceptual Frameworkmentioning
confidence: 99%
“…In a coastal context, research has shown that physical alteration and loss of coast often affect localized conceptions of identity and belonging (O'Collins 1990, Burley et al 2007, Graham et al 2014. A recent study from Korsra, Micronesia (Monnereau and Abraham 2013) illustrates that coastal erosion can have a series of adverse consequences at the local level.…”
Section: Introductionmentioning
confidence: 99%